2022
DOI: 10.3389/fmed.2022.875341
|View full text |Cite
|
Sign up to set email alerts
|

Blood HDAC4 Variation Links With Disease Activity and Response to Tumor Necrosis Factor Inhibitor and Regulates CD4+ T Cell Differentiation in Ankylosing Spondylitis

Abstract: PurposeHistone deacetylase 4 (HDAC4) regulates the progression of autoimmune diseases. This study aimed to further investigate the correlation between HDAC4 and Th cells, inflammation, disease activity, and treatment response in patients with ankylosing spondylitis (AS).MethodsA total of 132 active patients with AS were enrolled, of whom 54 patients received TNF inhibitor (TNFi) and 78 patients received NSAID. Serum HDAC4 was measured by ELISA in patients with AS before treatment (W0) and at week (W)4, W8, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…We note that the predictor CpGs annotate to genes associated with MHC class I (HLA-C) and cell migration (TSPEAR, NID2) 54,55 for VDZ and macrophage function (RHOJ, MARK3 and PCGF3) [56][57][58][59][60][61] and polarization (PKNOX1 and MRC1) [62][63][64] , histone remodeling and Th17differentiation (HDAC4) [65][66][67][68][69] and TGF-β signaling (SMAD1 and EBF3) [70][71][72][73][74][75][76][77] for USTE.…”
Section: Discussionmentioning
confidence: 99%
“…We note that the predictor CpGs annotate to genes associated with MHC class I (HLA-C) and cell migration (TSPEAR, NID2) 54,55 for VDZ and macrophage function (RHOJ, MARK3 and PCGF3) [56][57][58][59][60][61] and polarization (PKNOX1 and MRC1) [62][63][64] , histone remodeling and Th17differentiation (HDAC4) [65][66][67][68][69] and TGF-β signaling (SMAD1 and EBF3) [70][71][72][73][74][75][76][77] for USTE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that HDACs are involved in immune reactions. HDAC4 negatively regulates the polarization of naive CD4+ T cells toward the Th17 phenotype ( 120 ), while HDAC6 induces IL-13 expression through AP-1, leading to the polarization of M2 macrophages ( 121 ). Sirtuin 2 (SIRT2), a member of the NAD+-dependent histone deacetylase family, promotes the deacetylation of p70S6K, activates the mTORC1/HIF-1α/RORγ T pathway, inhibits the production of IL-2 by CD4+ T cells, and promotes their differentiation into Th17 cells ( 122 ).…”
Section: Regulation Of the Immune Microenvironmentmentioning
confidence: 99%